2021
DOI: 10.1039/d1cp04394c
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity reversals and their effect on bonding in the low-lying electronic states of cyclooctatetraene

Abstract: Aromaticity reversals and their effect on chemical bonding in the low-lying electronic states of cyclooctatetraene (COT) are investigated through a visual approach which examines the variations in isotropic magnetic shielding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
0
17
2
Order By: Relevance
“…The bond between the shared carbon atoms is completely deshielded (see also the S 1 contour plots in Figure 2), and the σ iso (r) = +16 ppm isosurface features "holes" next to these carbon atoms. Similarly to the shielding pictures observed in the S 2 states of benzene 15 and cyclooctatetraene, 16 in the S 2 state of naphthalene, the interior of the carbon framework is wellshielded all over, which suggests a high level of aromaticity. The more shielded regions close to peripheral carbon−carbon bonds in S 2 are displaced toward the interiors of two rings; higher shielding is observed next to the bonds between carbon atoms in β positions and over the bond between the shared carbon atoms (see the S 2 contour plots in Figure 2).…”
Section: Resultsmentioning
confidence: 57%
“…The bond between the shared carbon atoms is completely deshielded (see also the S 1 contour plots in Figure 2), and the σ iso (r) = +16 ppm isosurface features "holes" next to these carbon atoms. Similarly to the shielding pictures observed in the S 2 states of benzene 15 and cyclooctatetraene, 16 in the S 2 state of naphthalene, the interior of the carbon framework is wellshielded all over, which suggests a high level of aromaticity. The more shielded regions close to peripheral carbon−carbon bonds in S 2 are displaced toward the interiors of two rings; higher shielding is observed next to the bonds between carbon atoms in β positions and over the bond between the shared carbon atoms (see the S 2 contour plots in Figure 2).…”
Section: Resultsmentioning
confidence: 57%
“…It is interesting in this context to note that C 2 was of direct relevance to an earlier description of the bonding in [1.1.1]­propellane in terms of three-center two-electron “σ-bridged π bonds,” arising from the interaction of the MOs on a C 2 moiety and on the three methylene (CH 2 ) fragments . In conjugated cyclic systems with higher-energy π electrons, such as cyclobutadiene, the balance between the two terms in eq can change in favor of the negative second term above and below the ring, leading to the appearance of a distinctly deshielded dumbbell-shaped region which decreases shielding over bonds and can be associated with antiaromaticity. , On the other hand, strongly shielded central regions have been observed in shielding calculations on singlet excited states of benzene and cyclooctatetraene …”
Section: Introductionmentioning
confidence: 95%
“…21,22 On the other hand, strongly shielded central regions have been observed in shielding calculations on singlet excited states of benzene 22 and cyclooctatetraene. 23 In order to understand better the bonding pattern established within the very tight space inside the compact propellane cage, we compare the isotropic magnetic shielding distribution around [1.1.1]propellane to those around bicyclo[1.1.1]pentane, in which the hydrogen atoms connected to each bridgehead carbon atom (C b ) prevent the establishment of a C b −C b bond, as well as to those around tetrahedrane, the hypothetical hydrocarbon featuring the smallest carbon cage, and around bicyclo[1.1.0]butane and cyclopropane, the smallest examples of molecules with two fused and one three-membered carbon rings, respectively. We also examine the spatial variations around [1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational experience has shown that isotropic shielding distributions similar to those in the electronic ground states of benzene and square cyclobutadiene are observed in other electronic states and other conjugated rings; these types of distribution can be used for the unambiguous and semiquantitative classification of the local degree of aromaticity not only of the ground but also of low-lying excited ππ* electronic states of cyclic conjugated systems and provide a convenient tool for studying excited state aromaticity reversals. [13,15,19,[25][26][27][28][29] As shown in Figures 1-4, in both of C 6 H 6 and C 4 H 4…”
Section: Chemphyschemmentioning
confidence: 87%